Pola Asuh Pada Balita Gizi Baik Dan Gizi Buruk Di Desa Klumprit Kecamatan Mojolaban Kabupaten Sukoharjo - Megaasmoro, Swari; , Muwakhidah, SKM, M.Kes; , Kristien Andriani, SKM, M.Si (2014)
Introduction: parenting on children toddlers are always related to the feeding that eventually will contribute its nutrition value status. The lack of intake of nutrients and the presence of infectious diseases is the direct cause of the occurrence of malnutrition. Toddler nutrition data, based on the village of Klumprit has a percentage of poor nutrition status of 2,73%, 7%, less nutrients. Klumprit village has the highest percentage of toddler bad nutrition in the region work Puskesmas Mojolaban Objective: know the description of parenting a toddler good nutrition and malnutrition in Klumprit village of Mojolaban town in Sukoharjo Regency. Research methods: qualitative descriptive nature Research in methods of indepth interview and subject in this study is the mother who has toddlers aged 12 to 59 months with good nutritional status and poor nutritional status and its not working. The subject consists of 3 respondents Toddler Nutrition and nutritional toddler bad respondents 3. The research was carried out in Klumprit village of Mojolaban town in Sukoharjo Regency. Results: parenting mothers in feeding practices of good nutrition and toddler malnutrition not much different except in the awarding of the fruit, the respondents rarely give bad nutrition toddler fruit toddler. The practice of exclusive breast feeding, there were 2 respondents toddler malnutrition do not provide exclusive ASI to toddler. Health maintenance practices against toddler toddler respondents malnutrition not as good as the good nutritional toddler respondents always pay close attention to hygiene and health toddler, whereas the practice of monitoring the growth of children, based on last year's respondents one KMS Toddler Nutrition and nutritional toddler bad respondents actively carry toddler into the posyandu, but there is 1 respondent malnutrition that 4 times not brought toddler to the posyandu. Conclusion: the mother's parenting toddlers malnutrition compared to maternal parenting toddlers good nutrition, can be seen from the practice of the mother in the granting of the fruit to a toddler, exclusive breast feeding, growth monitoring and health care toddlers